PENINGKATAN MANAJEMEN SUMBER DAYA MANUSIA, KAPASITAS PRODUKSI, DAN PEMASARAN PRODUK ECOPRINT BANK SAMPAH SRAYAN MAKARYA - Praptapa, Agung; Gumintang, Bagas; Nikmah, Filda Khoirun; Ramadhan, Muhammad Syah Fibrika (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
This service is located at the Srayan Makarya Waste Bank, which is located on Jalan Gunung Wilis RT 01 RW 02, Bobosan Village, North Purwokerto District. Public Relations of Srayan Waste Bank, The first problem faced by Srayan Makarya Waste Bank is inadequate human resources. In order to fulfil human resources in the Srayan Makarya Waste Bank eco-print business, training must be provided. The second problem the Srayan Makarya Waste Bank faces is inadequate production capacity due to the small number of steamers for boiling cloth. The third problem is more marketing for eco-print products from the Srayan Makarya Waste Bank. The proposal for this activity is to improve the quality of human resources, increase production capacity, and increase and expand the market for Srayan Makarya Waste Bank's eco-print fabric. The obligatory output is a scientific article submitted at a national/international seminar by LPPM Unsoed and submitted to a proceeding. Meanwhile, the additional output is an activity video.